NaCS-PDMDAAC immobilized autotrophic cultivation of Chlorella sp. for wastewater nitrogen and phosphate removal - Zeng, X.; Danquah, Michael; Zheng, C.; Potumarthi, R.; Chen, X.; Lu, Y. (Elsevier BV, 2012)
The unicellular green microalgae, Chlorella sp., entrapped in sodium cellulose sulphate/poly-dimethyl-diallyl-ammonium chloride (NaCS-PDMDAAC) to create microalgae capsules were used to remove total nitrogen (T-N) and phosphate (PO 4 3--P) from artificial wastewater. Batch and semi-continuous cultivations with capsules recycling were carried out in shake flasks within an illuminated incubator. Experimental results showed that the NaCS-PDMDAAC capsules have desirable biophysical properties such as good mechanical stability, biocompatibility with the microalgae cells resulting in biomass enrichment within the capsules, and high substrate concentration tolerance. NaCS-PDMDAAC Chlorella sp. capsules displayed a considerable high T-N and PO 4 3--P removal rate of 12.56 and 10.24mg/g biomass per day respectively. The developed immobilized microalgae system has the potential for continuous wastewater treatment operation with reduced downstream operation cost due to the large size of the capsules being 5-6mm.